Basic principles of confocal microscopy of cаlcium signals - Shkryl, V. M. (Biophysical Bulletin, 2017)
Background: The study of fast processes occurring in living cells, for example, the dynamics of calcium ions or other ions, is actual for modern biophysics, physiology and medicine and can be carried out by laser scanning confocal microscopy. Confocal microscopy as a method of studying biological objects has a number of features requiring an understanding of the delicate mechanisms underlying it.Objectives: The aim of the work is the description of principles and details of measurements of calcium signals in the living cells using laser scanning confocal microscopy and fluorescent indicators.Materials and methods: The analysis of the methodological and practical aspects of studies of calcium signals was carried out by confocal microscopy in the work.Results: Confocal microscopy allows to study the changes in the concentration of free calcium within the cell and even a small part of it by a fluorescent dye, which increases the contrast in comparison with conventional fluorescence microscopy through an additional confocal aperture located in the front of the detector and the use of laser light source and scanning the object. To register calcium signals it is necessary to make a selection of a number of adequate parameters: the registration frequency, the size of a single scanning element (pixel), the sensitivity of the detector, the intensity of laser irradiation, the diameter of the confocal gap, the corresponding filters for exciting and emitting the fluorescent dye used and the corresponding dichroic mirror. An important stage of a setup of a confocal system is the determination of the value of the scattering function of a point. Compensation of the process of bleaching of the fluorescence dye and reduction of phototoxicity, minimization of the scattering process of the image allow to increase a reproducibility of the experiments.Conclusions: Using modern laser scanning confocal microscopes for registration of calcium signals from a small group of channels (for example, rianodine receptors) or the cell part, it is necessary to carefully select the parameters of the hardware setup, which are determined by the nature of the object of study and the peculiarities of the experimental conditions. This will allow to receive the reliable information about the functioning of both individual channels and the mechanisms of Ca2+ signaling of the whole cell or its part.